ANALISA ALGORITMA C4.5 DALAM MENENTUKAN FAKTOR YANG MEMPENGARUHI MUNCULNYA PROFESSIONAL BLOGGER - Robby Robby (JURNAL ILMIAH INFORMATIKA, 2019)
The growing of information technology and technological advance has made a lot of changes in media. Blogs are the recent emerging mediaand data information.They are provided for ideas and exchanging opinions. We apply C4.5 algorithm by applying decision tree with 0.25 confidence to determine the ratio from attributes that influence the professional blogger.The dataset uses blogger data from UCI Machine Learning Repository. C4.5 algorithm calculating entropy and information gain to produce a decision tree. Professional Blogger which attributes as destination attributes, while the degree, political caprice, topics, local media turnover, and local political social spaces as a source attribute to obtain the root node and other nodes.